Activity patterns of breeding Hen Harriers Circus cyaneus assessed using nest cameras. Issue 4 (2nd October 2017) - Fernández-Bellon, Darío; Wilson, Mark W.; Irwin, Sandra; Kelly, Thomas C.; O'Mahony, Barry; O'Halloran, John
ABSTRACT: Nest camera footage from 13 Hen Harrier Circus cyaneus nests was analysed to document patterns of adult attendance, incubation, brooding and prey delivery rates. Nest attendance was high throughout the incubation stage and began to decrease when chicks were five days old. Chick provisioning increased gradually after hatching and peaked when the chicks were five days old. Daily activity rates were highest during the middle of the day, from 08:00 to 19:00 hours.